Changes in eudaimonic well-being and the conserved transcriptional response to adversity in younger breast cancer survivors. (May 2019) - Boyle, Chloe C.; Cole, Steve W.; Dutcher, Janine M.; Eisenberger, Naomi I.; Bower, Julienne E.
Highlights: A mindfulness meditation practice was associated with increased eudaimonic well-being in a sample of breast cancer survivors. Increases in eudaimonic well-being correlated with decreases in the Conserved Transcriptional Response to Adversity (CTRA). Eudaimonia-related CTRA reductions were driven primarily by increased expression of anti-viral and antibody-related genes. The intervention was associated with reduced pro-inflammatory gene expression. Changes in CTRA gene expression were not related to changes in distress or hedonic well-being. Abstract: Background: The conserved transcriptional response to adversity (CTRA), characterized by increased expression of proinflammatory genes and decreased expression of antiviral and antibody-related genes, is upregulated in the context of chronic adversity and distress and has been linked to cancer progression. Several studies suggest that the CTRA may also be down-regulated in association with some positive psychological states, particularly eudaimonic well-being. However, it is not clear if the link between inter-individual differences in the CTRA and eudaimonic well-being can be extended to intra-individual change. Using a standardized mindfulness-based intervention, the current study tested whether mindfulness-related increases in eudaimonic well-being related to intra-individual reduction in the CTRA in a sample of younger breast cancer survivors. Methods: Participants were 22 women who had been diagnosed and treated for early-stage breast cancer at or before age 50 (Mage  = 46.6 years) and had no evidence of active disease. Women completed self-report questionnaires and provided peripheral blood samples before and after a 6-week mindfulness meditation intervention. Regression analyses were used to quantify associations between the magnitude of change in eudaimonic well-being and the magnitude of change in the global CTRA score. Results: Women reported significant increases in eudaimonic well–being and showed decreased expression of the pro-inflammatory subcomponent of the CTRA from pre- to post-intervention. The magnitude of increase in eudaimonic well-being was associated with the magnitude of decrease in the composite CTRA score, and this relationship was driven primarily by increased expression of the antiviral/antibody-related CTRA subcomponent. While the intervention was also associated with reduced depressive symptoms, there was no association between change in depressive symptoms and change in the overall CTRA composite score or either of its subcomponents. Conclusions: Results are consistent with the hypothesis that eudaimonic well-being may be an important mechanism in interventions aimed at enhancing health in vulnerable groups, and contribute to our understanding of how psychological well-being may influence physical health in cancer patients.